Bone morphogenetic protein signaling in breast cancer progression. (4th March 2019) - Chi, Lap Hing; Burrows, Allan D.; Anderson, Robin L.
Abstract: Breast cancer is the most prevalent type of cancer amongst women worldwide. The mortality rate for patients with early-stage breast cancer has been decreasing, however, the 5-year survival rate for patients with metastatic disease remains poor, currently at 27%. Here, we have reviewed the current understanding of the role of bone morphogenetic protein (BMP) signaling in breast cancer progression, and have highlighted the discordant results that are reported in different studies. We propose that some of these contradictory outcomes may result from signaling through either the canonical or non-canonical pathways in different cell lines and tumors, or from different tumor-stromal interactions that occur in vivo .